A Case Study: Sediment Erosion in Francis Turbines Operated at the San Francisco Hydropower Plant in Ecuador - Cristian Cruzatty; Darwin Jimenez; Esteban Valencia; Ivan Zambrano; Christian Mora; Xianwu Luo; Edgar Cando (Energies, 2021)
The operation of various types of turbomachines is importantly affected by sediment erosion. Francis turbines used for power generation typically suffer said effects due to the fact that they are used in sediment-laden rivers and are usually operated disregarding the long-term effect of the erosion on turbine performance. This investigation seeks to study the erosion rate for the main components of the turbines located at San Francisco hydropower plant in Pastaza, Ecuador. A sediment characterization study was performed in order to determine the properties of the particles present in Pastaza River and accurately predict their effect on the turbine flow passages. A numerical approach combining liquid–solid two-phase flow simulation and an erosion model was used to analyze the erosion rates at different operating conditions and determine wear patterns in the components. As expected, the results indicated that an increase in the erosion rate was obtained for higher intake flows. However, a dramatic increase in the erosion rate was observed when the turbine was operated at near-full-load conditions, specifically when guide vane opening exceeded a 90% aperture.